2015
DOI: 10.1371/journal.pone.0121034
|View full text |Cite|
|
Sign up to set email alerts
|

Interacted QTL Mapping in Partial NCII Design Provides Evidences for Breeding by Design

Abstract: The utilization of heterosis in rice, maize and rapeseed has revolutionized crop production. Although elite hybrid cultivars are mainly derived from the F1 crosses between two groups of parents, named NCII mating design, little has been known about the methodology of how interacted effects influence quantitative trait performance in the population. To bridge genetic analysis with hybrid breeding, here we integrated an interacted QTL mapping approach with breeding by design in partial NCII mating design. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…Considering all available mating designs that have been used in quantitative genetics, hybrids from a full diallel design with n parents would be one of the best MHPs, as the full set hybrids can be divided into three subsets, two diallels and one NC II, as needed. As such an attempt with a limited number of hybrids, a partial NC II was used for QTL mapping to test effects associated with traits, and the significant effects identified by empirical Bayesian were used to estimate genetic effects for the missing F 1 s with elite parents and hybrids predicted37. The generated hybrids, along with the parental genotype and phenotype, can be used to predict the missing hybrids and the rest hybrids.…”
Section: Multiple-hybrid Populations (Mhp) For Gwasmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering all available mating designs that have been used in quantitative genetics, hybrids from a full diallel design with n parents would be one of the best MHPs, as the full set hybrids can be divided into three subsets, two diallels and one NC II, as needed. As such an attempt with a limited number of hybrids, a partial NC II was used for QTL mapping to test effects associated with traits, and the significant effects identified by empirical Bayesian were used to estimate genetic effects for the missing F 1 s with elite parents and hybrids predicted37. The generated hybrids, along with the parental genotype and phenotype, can be used to predict the missing hybrids and the rest hybrids.…”
Section: Multiple-hybrid Populations (Mhp) For Gwasmentioning
confidence: 99%
“…As we calculated in the precious section, genotypes for 4,500 hybrids can be inferred from 100 parental lines genotyped, the former being 45 folds larger. In Brassica napus , 205 SSR markers were used to examine the polymorphisms among 441 parents (298 sterile and 143 restorer lines), and the genotypes for the partial NC II hybrids could be then deduced from their parents37, with 8 main-effect and 37 interacted QTL identified for oil content, which could be used to predict 10 elite restorer lines, 10 elite sterile lines and 10 elite hybrids.…”
Section: Multiple-hybrid Populations (Mhp) For Gwasmentioning
confidence: 99%
See 2 more Smart Citations
“…All the effects in the above model were estimated by empirical Bayes 61 . Results from Monte Carlo simulation studies showed that these estimates were unbiased 61 62 63 . The significance threshold of the logarithm of odds (LOD) score was set at 3, which is equivalent to the significance level of 0.0002 63 .…”
Section: Methodsmentioning
confidence: 99%